Motivasi, Humanisme, dan Transendensi dalam Sekumpulan Puisi Felix Mencuci Piring Karya Tengsoe Tjahjono - Kusmiyati, Yatik; Supratno, Haris; Indarti, Titik (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the poems contained in the collection of poems Felix Mencuci Piring by Tengsoe Tjahjono. Literary reception is a literary genre that examines literary texts by considering the reader as the person giving the welcome or response. Readers in giving remarks and responses are influenced by factors of space, time and social group. The data collection technique in this research uses library or document techniques. The results of this research show that in a collection of poems, Felix Mencuci Piring is a poem that is full of motivation, humanization and transcendence. The poems in the book awaken the reader's self-awareness to always be careful, caring, and aware of God presence in every aspect of life.